THE WORK ENVIRONMENT AND MOTIVATION IN UNIVERSITY TEACHERS - VADILLO DIONICIO, Hellen Edith (2023)
The work environment and motivation are an important part of educational development. On the one hand, it is known that motivation in teachers is classified as a fundamental piece for the organization to function without any problem. It is also known that the work environment is also one of the determining factors that influence the behavior of the members of the education and that condition the levels of work motivation and professional performance; It is necessary to raise the research that seeks to establish the relationship between the work environment and motivation in the teachers of the Professional School of Physical Education of the Faculty of Education of the National University of San Marcos in 2018 for which it has been designed a descriptive correlation investigation under a quantitative approach where the existence of a relationship with a Pearson correlation coefficient = 0.952 and a significance coefficient of 0 was found, which is why it can be stated that there is a relationship between organizational climate and motivation